2017
DOI: 10.1177/0003319717699329
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis and Cardiovascular Risk: Correlation Between Psoriasis and Cardiovascular Functional Indices

Abstract: Evidence suggests that psoriasis together with other cardiovascular (CV) risk factors is associated with increased vascular morbidity, but it is not clear whether psoriasis is an independent risk factor. Consecutive patients (n = 33; 35.6 ± 5.7 years; 13 females) with mild psoriasis (Psoriasis Area and Severity Index <10) without comorbidities and 33 healthy participants (36.3 ± 5.9 years; 15 females) were enrolled. Both groups underwent echocardiography, speckle tracking (2-dimensional strain echocardiography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 44 publications
1
32
0
Order By: Relevance
“…Apart from PsA, spondyloarthritis includes ankylosing spondylitis (AS), inflammatory bowel disease (IBD)‐related arthritis and undifferentiated spondyloarthritis. PsA, as well as skin psoriasis, is associated with co‐morbidities including cardiovascular disease, obesity and metabolic syndrome …”
Section: Introductionmentioning
confidence: 99%
“…Apart from PsA, spondyloarthritis includes ankylosing spondylitis (AS), inflammatory bowel disease (IBD)‐related arthritis and undifferentiated spondyloarthritis. PsA, as well as skin psoriasis, is associated with co‐morbidities including cardiovascular disease, obesity and metabolic syndrome …”
Section: Introductionmentioning
confidence: 99%
“…44 In another study, both cIMT and hsCRP were associated with bilirubin levels in patients with psoriasis. 45 In this issue of the journal, Dattilo et al 57 assessed cardiac and vascular abnormalities in patients with psoriasis. The study compared 33 young patients with mild psoriasis (free of CV risk factors and overt CV disease) and 33 well-matched healthy volunteers.…”
mentioning
confidence: 99%
“…They found that traditional echocardiographic indices were similar between the 2 groups, while more modern echocardiographic techniques, such as the global longitudinal strain, were altered in patients with mild psoriasis and correlated with disease duration and age at diagnosis. 57 Moreover, arterial stiffness (assessed by carotid-femoral pulse wave velocity), a reliable index of vascular disease, was also altered in patients with psoriasis. 57 Dattilo et al 57 provided clinically meaningful data on the effect of mild psoriasis on the CV system, highlighting the importance of using modern echocardiographic indices to recognize subclinical heart disease.…”
mentioning
confidence: 99%
See 2 more Smart Citations